Effects of policies on yam production and consumption in Nigeria - Adesiyan, O.F.; Adesiyan, A.T.; Bamire, A.; Ousmane, C.; Asiedu, Robert (Wiley, 2016)
Several efforts have been made through research, government programs and Non-Governmental Organisations (NGO) interventions to improve yam production in Nigeria. In addition, some policies targeted at improving agricultural production have weakened the production and consumption of different commodities, especially yam. This study analyzed the effects of policy changes on yam production and consumption in Nigeria. A multi-stage sampling technique was used to select 700 respondents for the study. Primary data was collected using pre-tested structured questionnaire while interview guide was used to collect information in a Focus Group Discussion. Data were analyzed using Multi-Market Model.